Corrosion Studies of Thermal Sprayed HA and HA+Al2O3-TiO2 Coatings on 316L Stainless Steel - Walia, Bhupesh; Singh Sarao, T. P.; Grewal, J. S. (Asian Review of Mechanical Engineering, 2014)
This study was performed to evaluate corrosion behavior of thermal sprayed hydroxyapatite (HA) and hydroxyapatite+Alumina-titania (HA+Al2O3-TiO2) coatings on 316L stainless steel (316L SS) implant material. HA powder was mixed with Al2O3-TiO2 in 60:40 wt. % for depositing HA+Al2O3-TiO2 composite coatings. The coatings were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM)/energy-dispersive X-ray spectroscopy (EDS) analyses. Tafel and Potentiodynamic techniques were used to access the in-vitro corrosion behavior of two coatings and un-coated 316L SS in Hank’s solution. The corrosion resistance of 316L SS showed a significant improvement after the deposition of coatings.